PELAKSANAAN PENGAWASAN TERHADAP PRODUK MAKANAN IMPOR OLEH BALAI BESAR PENGAWAS OBAT DAN MAKANAN (BBPOM) DI KOTA PEKANBARU - Mardiah "; Ernawaty " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Much of the food that has been imported into Indonesia without clear information on its packaging. Whether it's because without a marketing authorization and the product is damaged or expired . All of these products are mostly imported illegally from neighboring Malaysia . Often the data information contained in the packaging of food products imported manipulated is to hide the use of materials - hazardous chemicals contained in food in between formalin , borax , and rhodamine -b . Until now , monitoring the implementation of the food and beverage imports in Pekanbaru still felt very minimal . Idealitanya BBPOM protect consumers of imported foods that contain harmful chemicals in Pekanbaru . Knowledge society is still not sufficient to be able to select and use imported products appropriately , correctly and safely . Hence the importance of this issue in this paper the authors take the title Implementation Supervision of Imported Food Products in Pekanbaru . The concept of the theory is that researchers use control . Supervision consists of food standards , assessment measures , and corrective actions . Source of qualitative data obtained , in the form of primary data and secondary data . Determination method used in this study was the informant snowball sampling , while the samples taken are Hall of POM in Pekanbaru especially the supervision and consumer protection . The method of data analysis was done qualitatively obtained by triangulation techniques . In collecting the data , the researcher used interview techniques , observation and documentation . The results showed that the monitoring of imported food products made with two methods , namely Pre Market Surveillance and Monitoring Post Market . Still many food products illegally imported and expired in addition to the factors of government oversight ( BBPOM ) is not tight . Therefore , the surveillance here BBPOM be very important in assessing the time of registration of the imported food products . Legal protection given to consumers is thus still less than optimal .Keywords : Monitoring , BBPOM , Food Import